Study of separation of rubidium and strontium by ion-exchange chromatography in HNO3 and HCl media for determination of their content and isotopic composition using ICP-MS - Trung, Huynh Van; Chien, Nguyen Xuan; Minh, Le Hong (Vietnam Journal of Chemistry, 2012)
Cliromatographic methods for separation of rubidium and strontium from each other and from matrix on cationit resin Biorad AG 50Wx8, 200-400 mesh are proposed. The elements were determined by ICP-MS Agilent 7500a. Rubidium, strontium and some of other elements were absorbed to the resin in 0.7 M HNO3 medium. Then, rubidium and strontium could be eluted at the same time or one after another with HCI solution, that has the different concentrations. The methods can be well applied for analysis of the content and isotopic composition of rubidium and strontium by ICP-MS.